Performance evaluation of waste glass in soil improvement: Influence of particle size of waste glass on mechanical, microstructural, and durability characteristics - Harun Akoğuz (Case Studies in Construction Materials)
The accumulation of waste glass (WG) from construction and demolition waste is detrimental to the environment due to its imperishable nature; therefore, it is crucial to investigate a sustainable way to recycle and reuse the WG. To address this issue, this study examined the mechanical strength, microstructural characteristics, and environmental durability—specifically under wet-dry (WD) and freeze-thaw (FT) cycles—of WG obtained from construction and demolition waste, with a focus on its suitability as a binding material for soil improvement applications. Firstly, sand and WG were mixed, and an alkali solution was injected into the mixture, considering various parameters, including WG particle size, mixing proportions, sodium hydroxide (NaOH) concentration, and curing time. Subsequently, the effect of WG grain sizes on micromorphology characteristics and mineralogical phases was evaluated before and after the treatment through X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), and ultrasonic pulse velocity (UPV). The results revealed that reducing the WG particle size and increasing the WG/S ratio significantly improved the strength of the WG-treated samples. Additionally, decreasing the NaOH concentration and extending the curing time also positively influenced their strength. The UCS test results indicate that the particle size of WG significantly influenced the strength development of the samples, as the maximum compressive strength increased from 1.42 MPa to 7.82 MPa with the decrease in particle size. Although the maximum UCS values of the samples varied with different WG particle sizes, the values exceed the minimum criterion of 0.80 MPa required for use as a road substructure, as specified in the ASTM D4609 standard. Moreover, as WG grain size decreased, more geopolymer gels formed, continuing to fill the voids and making the overall structure denser, and the changes during geopolymerization were confirmed by XRD, SEM, FTIR, and UPV analysis. The optimum WG/S ratio was found to be 20 %, with strength increasing by approximately 3.88 times higher as the WG/S ratio shifted from 5 % to 20 %. In addition, the optimum NaOH concentration was determined to be 10 M, as higher molarities led to a decrease in strength. Moreover, UPV results indicate that WG-treated sand soils exhibited UPV values 9.4–13 times greater than untreated soils. The WD and FT test results indicate that WG-treated samples experienced more rapid disintegration in the WD cycle than in the FT cycle; however, a decrease in WG particle size resulted in reduced disintegration effects in both WD and FT conditions. In both the FT and WD cycles, the declining trend exhibited a stable tendency around the eighth cycle. Nevertheless, the WD cycling damage considerably intensified disintegration, causing a profound deterioration in the structural integrity of the samples. As a result, repeated WD cycles lead to the formation of microcracks, which progressively weaken soil aggregation and reduce the overall strength of the samples. Consequently, this green and simple soil improvement technique can provide more inspiration for reducing waste and building material costs through efficient use of construction and demolition waste.